Overall diet quality and age-related macular degeneration - Montgomery, Martha P. (2010)
OBJECTIVE: To examine overall diet quality in relation to advanced age-related macular degeneration (AMD). METHODS: This case-control study identified 437 advanced AMD patients and 259 unrelated controls using stereoscopic color fundus photographs. Participants were predominantly non-Hispanic white men and women from North Carolina and Tennessee. A 97-item Block food frequency questionnaire was used to gather diet information, and overall diet quality was measured using the Healthy Eating Index (HEI) and Alternate Healthy Eating Index (AHEI). RESULTS: Participants in the highest quartile of diet quality had significantly reduced odds of AMD according to the AHEI score (0.54, 95% confidence interval 0.30 – 0.99) and non-significantly reduced odds of AMD according to the HEI (0.75, 0.41 – 1.38). Odds of AMD were also 51% lower in the highest quartile of fish intake compared to the lowest quartile (odds ratio = 0.49, 0.26 – 0.90). CONCLUSIONS: We found that advanced AMD was significantly related to overall diet quality. The AHEI score may be a useful instrument for assessing AMD risk due to diet, and it could potentially be improved by incorporating more specific information regarding micronutrient intake.